The Relationship Between Work Stress, Supervisor Support, Mindfulness, and Employee Well-Being on Job Performance Outcomes - Novianty Djafri; Dian Arlupi Utami; Noorhani Dyani Laksmi; Tresna Kusumawati (Malaqbi Publisher, 2026)
This study examines the relationship between work stress, supervisor support, mindfulness, employee well-being, and job performance outcomes. Drawing on the Job Demands–Resources (JD-R) framework, this research investigates how work stress as a job demand and supervisor support and mindfulness as organizational and personal resources influence employee well-being and performance. A quantitative approach was employed using a cross-sectional survey design, with data collected from 250 employees across various sectors. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that work stress has a significant negative effect on both employee well-being and job performance. In contrast, supervisor support and mindfulness show significant positive effects on well-being and performance. Furthermore, employee well-being significantly influences job performance and serves as a key mediating variable in the relationships between work stress, supervisor support, mindfulness, and performance outcomes. These findings highlight the importance of reducing workplace stress while enhancing organizational support and individual mindfulness practices to improve employee well-being and productivity. The study contributes to the literature by integrating job demands, organizational resources, and personal resources into a comprehensive model, offering practical implications for organizations aiming to achieve sustainable performance through employee well-being.